Clinical Profile of Leprosy in Post-elimination Era in a Tertiary Care Hospital - Gurung, Tsering Dolma; Chapagain, Laxman; Paudel, Upama (Journal of Institute of Medicine Nepal, 2024)
Introduction Leprosy is a chronic disease that primarily affects peripheral nerves and skin. It has a long incubation period and clinical presentations are variable leading to deformities and social stigma. Leprosy was eliminated in Nepal in 2010 AD. This study was undertaken to determine the demographic and clinical profile of Leprosy in the past three years. Methods A retrospective observational study was conducted in the Department of Dermatology and Venereology, Tribhuvan University Teaching Hospital. Records of all the newly diagnosed leprosy patients attending the Out-Patient Department from April 2021 to March 2023 were reviewed retrospectively and analyzed. Results There were 109 newly diagnosed leprosy cases among which majority were males. The maximum clinical diagnosis was lepromatous leprosy and 100 (91.74%) cases were multibacillary. Type 1 lepra reaction was seen in 11 (10.09%) patients and 12 (11%) patients had type 2 lepra reaction. Slit skin smear was positive in 75 (68.80%) patients. On clinical examination, peripheral nerves were palpable in 92 (84.4%) patients with ulnar nerve being the most common palpable peripheral nerve. Type 1 deformity was present in 55 (50.45%) patients and 18 (16.51%) patients had type 2 deformity. Claw hand was the most common type 2 deformity observed. Conclusion Though leprosy has been eliminated in Nepal, there are still considerable cases of Leprosy. Higher number of cases with multibacillary disease and increasing number of Lepra reaction is an alarming sign.